Ex vivo recapitulation of trauma-induced coagulopathy and preliminary assessment of trauma patient platelet function under flow using microfluidic technology. Issue 3 (March 2016) - Li, Ruizhi; Elmongy, Hanna; Sims, Carrie; Diamond, Scott L.
Abstract : BACKGROUND: Relevant to trauma-induced coagulopathy diagnostics, microfluidic assays allow controlled hemodynamics for testing of platelet and coagulation function using whole blood. METHODS: Hemodilution or hyperfibrinolysis was studied under flow with modified healthy whole blood. Furthermore, platelet function was also measured using whole blood from trauma patients admitted to a Level I trauma center. Platelet deposition was measured with PPACK-inhibited blood perfused over collagen surfaces at a wall shear rate of 200 s −1, whereas platelet/fibrin deposition was measured with corn trypsin inhibitor–treated blood perfused over tissue factor (TF)/collagen. RESULTS: In hemodilution studies, PPACK-treated blood displayed almost no platelet deposition when diluted to 10% hematocrit with saline, platelet-poor plasma, or platelet-rich plasma. Using similar dilutions, platelet/fibrin deposition was essentially absent for corn trypsin inhibitor–treated blood perfused over TF/collagen. To mimic hyperfibrinolysis during trauma, exogenous tissue plasminogen activator (50 nM) was added to blood before perfusion over TF/collagen. At both venous and arterial flows, the generation and subsequent lysis of fibrin were detectable within 6 minutes, with lysis blocked by addition of the plasmin inhibitor, ε-aminocaproic acid. Microfluidic assay of PPACK-inhibited whole blood from trauma patients revealed striking defects in collagen response and secondary platelet aggregation in 14 of 21 patients, whereas platelet hyperfunction was detected in three of 20 patients. CONCLUSION: Rapid microfluidic detection of (1) hemodilution-dependent impairment of clotting, (2) clot instability because of lysis, (3) blockade of fibrinolysis, or (4) platelet dysfunction during trauma may provide novel diagnostic opportunities to predict trauma-induced coagulopathy risk. Abstract : Supplemental digital content is available in the text.